2015
DOI: 10.18388/abp.2015_1015
|View full text |Cite
|
Sign up to set email alerts
|

Screening for genetic mutations in LDLR gene with familial hypercholesterolemia patients in the Saudi population

Abstract: Familial hypercholesterolemia (FH) is caused by genetic defects involving the low density lipoprotein-receptor (LDL-R), predisposing affected people to premature atherosclerotic cardiovascular disease and death. The aim of the present study was to assess certain exons in the LDLR gene mutation detection analysis affecting in the Saudi population with FH. This case-control study was carried out with 200 subjects; 100 were FH cases and 100 were healthy controls. Five mL of venous blood samples were collected fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 15 publications
1
11
0
Order By: Relevance
“…In our study, we represented the first description of heterozygous mutations in the exon 4 of the gene for LDLR in Vietnamese patients with hypercholesterolemia. In previous studies, the prevalence of [1,2], made the comparison, in our study, the results showed that 29 cases of 40 cases, counting for 72.5%, which was completely higher. In our initial study, all of 40 clinical samples were collected from FH patients, thus, we initial concluded that the 72.5% FH patients containing the mutation on exon 4 of the LDLR gene.…”
Section: Discussionsupporting
confidence: 59%
“…In our study, we represented the first description of heterozygous mutations in the exon 4 of the gene for LDLR in Vietnamese patients with hypercholesterolemia. In previous studies, the prevalence of [1,2], made the comparison, in our study, the results showed that 29 cases of 40 cases, counting for 72.5%, which was completely higher. In our initial study, all of 40 clinical samples were collected from FH patients, thus, we initial concluded that the 72.5% FH patients containing the mutation on exon 4 of the LDLR gene.…”
Section: Discussionsupporting
confidence: 59%
“…It is interesting to note that FH genetic diagnosis is happening almost all over the world, mainly within the scope of research projects, 30,[32][33][34][35][36][37] since only The Netherlands, Spain, and Uruguay have governmental approval for the identification of FH patients. 38,39 The fact that most variants are restricted to a continent was also an interesting finding, suggesting that population migration occurs mostly within the same continent.…”
Section: Discussionmentioning
confidence: 99%
“…Most prior publications regarding FH patients come from countries that have nationalized health care systems or socialized medicine, offering opportunities to standardize medical practice. 10,16,17 …”
Section: Discussionmentioning
confidence: 99%